Heterogeneous Analysis of the Nexus between Big Data Analytics and Value Co-Creation: Insight from Selected Service Businesses in Ghana - Otchere, Samuel Kofi; Tian, Hongyun; Paa Kwasi Coffie, Cephas; Hammond, Frank (Technium Social Sciences Journal, 2021)
The study examines big datas role analytics ininterfirm value co-creation in selected service businesses in Ghana by focusing specifically on the heterogenous big data characteristics. This is in response to the ongoing debate on value co-creation and big data nexus. Using data from 61 purposively sampled service businesses in Accra-Ghana, the structural equation model provides that; big data analytics positively influences interfirm value co-creation in the selected businesses. Further, aside from big data volume, all the other big data characteristics (velocity, veracity, value, and variety) also individually influence value co-creation. Therefore, this challenges businesses of all sizes to invest in the application of big data for strategic decisions like value co-creation. Again, although businesses should be willing to collaborate with others, big data teams should be fully equipped for optimal analytics.